Evaluasi Kualitas Desain Ruang Pada Kafe di Kota Batu Berdasarkan Persepsi Pengunjung - Khansa Rofilah; Dr. Eng. Ir. Herry Santosa, ST., MT., IPM (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
This study examines the space design quality at cafes in mountains area that highlight natural scenery. The research topic is evaluate visitor perception of optimizing the use of nature on the quality of cafe space design. The case studies are in three cafes in Batu City. Batu City is a tourist area that located in a mountains area. The method used is descriptive quantitative approach, data collecting through field surveys and questionnaires from respondents in each caf . Data analysis uses mean scores and the Sturgess formula to determine rating category intervals. The results show that the three cafes have different ratings. Cokelat Klasik Cafe received high ratings for utilizing openings, nature-inspired furniture, attractive wall materials, building forms that maximize views, and lighting and color choices. Monstera Cafe received high ratings for its window design showcasing scenery, door access, and appealing furniture design. NOI Coffee Cafe received high ratings for its door design, attractive lighting and colors, and overall quality of interior and exterior spaces. The results of the respondent’s assessment also show that elements of the utilizing openings cafe, lighting, and the furniture used are the element that has the most inf Keywords: visitor perception, natural scenery, Cafe space design, and Batu City